Wheat Cost-Return Budget in North Central Kansas - Lubben, Bradley D. (My University, 2000)
This publication provides estimated cost and returns for forward farm planning for wheat in north central Kansas.
MF2158_2000_10
Keywords: MF2158; Crops; Economics; MF